Peran Stabilitas Ketahanan Pangan sebagai Salah Satu Bentuk Tolak Ukur Keamanan di Masyarakat Pada Masa Pandemi Covid -19 - Dwi Atmoko , Dwi Atmoko; Fajarwati, Rona Apriana (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
Food security is a very important thing in people’s lives. Good food security will lead to a good social order as well. During the COVID-19 pandemic, the Indonesian state experienced a slump in various fields, which resulted in Indonesia’s economic growth experiencing a significant decline. The stability of food security with the transmission of the COVID-19 virus outbreak experienced obstacles and disruptions, starting from the inhibition of food production, distribution, and production transportation, including production support equipment which resulted in serious food availability problems. The Indonesian government in dealing with this pandemic outbreak has issued regulations or policies to suppress the spread of the COVID-19 virus by issuing Large-Scale Social Restrictions, but the impact or effect it causes is that many industrial sectors have finally closed their businesses, be it from the hotel, restaurant sector. or tourism, as well as malls or retail which in turn has an impact on the reduction of labor and the departure of industrial players. The benchmark for food security is highly dependent on the surrounding environment, both national and international domestic factors. If the two environments give a good effect, of course, food security will be achieved well. And vice versa if the environment is not good, then what will arise is food and other problems that surround it, including food sufficiency. Poor food security, especially for poor families ‘ food security is the emergence of negative actions such as crime and the like. The government in dealing with this problem has issued a quick policy by carrying out a program of economic recovery and transformation with the issuance of Presidential Regulation Number 82 of 2020 concerning the Corona Virus (COVID-19) Management Committee and National Economic Recovery whose aim is expected to restore existing economic conditions in order to achieve growth. stable and equitable economy in all lines of people’s lives.